Increasing The Efficiency Of Small Hydro Power Plant For Changing Water Flow - Rubes, Ondrej (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
This paper deals with increasing the efficiency of a small hydro power plant in a low power operation. Problem of the low power operation is low efficiency. Both, turbine and generator, are optimized for nominal power. On the other hand, in the low power operation they have low efficiency. The losses in generator are analysed and possible improvements are suggested. This should contribute to higher efficiency in the low power operation. Water turbine efficiency is showed for different water flows and ways to improve efficiency for lower flows are presented. Calculation of nominal efficiency and possible new higher efficiency is made.
Keywords: Small hydro power plant; Efficiency; Converter